Ancient DNA of the extinct lava shearwater (Puffinus olsoni) from the Canary Islands reveals incipient differentiation within the P. puffinus complex. - Oscar Ramirez (Public Library of Science (PLoS), 2010)
Background The loss of species during the Holocene was, dramatically more important on islands than on continents. Seabirds from islands are very vulnerable to human-induced alterations such as habitat destruction, hunting and exotic predators. For example, in the genus Puffinus (family Procellariidae) the extinction of at least five species has been recorded during the Holocene, two of them coming from the Canary Islands. Methodology/principal findings We used bones of the two extinct Canary shearwaters (P. olsoni and P. holeae) to obtain genetic data, for use in providing insights into the differentiation process within the genus Puffinus. Although mitochondrial DNA (mtDNA) cytochrome b sequences were successfully retrieved from four Holocene specimens of the extinct Lava shearwater (P. olsoni) from Fuerteventura (Canary Islands), the P. holeae specimens yielded no DNA. Only one haplotype was detected in P. olsoni, suggesting a low genetic diversity within this species. Conclusions The phylogenetic analyses based on the DNA data reveal that: (i) the "Puffinus puffinus complex", an assemblage of species defined using osteological characteristics (P. puffinus, P. olsoni, P. mauretanicus, P. yelkouan and probably P. holeae), shows unresolved phylogenetic relationships; (ii) despite the differences in body size and proportions, P. olsoni and the extant P. puffinus are sister species. Several hypotheses can be considered to explain the incipient differentiation between P. olsoni and P. puffinus.